CYCLOOXYGENASE -2 AND CANCER: A silent link with fatal ending - Zafar, Salman; Kehar, Shahnaz Imdad (International Journal of Pathology, 2018)
Abstract: Remarkable evolutions in pathogenic role of Cyclooxygenase-2 (COX-2) in tumorigenesis have divertedthe cancer research in the direction of COX-2 inhibitors. An expanding body of evidence indicates that downregulation of cyclooxygenase 2 will be an important strategy for preventing cancer because COX-2 catalyzes theformation of prostaglandins(PGs) and these prostaglandins have multiple effects that favor tumorigenesis. It isproved that during the process of chronic inflammation several cytokines and inflammatory mediators are releasedwhich act during the different stages of carcinogenesis. Among all these mediators COX 2 are the key player. COX2is found to be over expressed in several malignancies like colorectal carcinoma, squamous cell carcinomas of headand neck, carcinomas of urinary bladder, liver, stomach, breast as well as hematological malignancies. Our reviewarticle aims to summarize the role of COX 2 in various cancers and the mechanisms responsible for carcinogenesis.The informations gathered in this review are taken mainly from articles published in different internationaljournals.